The Phenomenon of Xenotransplantation in The Medical World in Terms of Potential, Risk, Ethics And Islamic Perspectives - Mulyawan, Rafmanuha Putri; Aliyah, Syifa Ripatul; Ramdhanawati, Vania Ulfa; Cahyanto, Tri; Kulsum, Yuni (Fakultas Sains dan Teknologi UIN Sunan Gunung Djati Bandung, 2024)
Transplantation is a process of transferring organs that are still functioning properly to replace organs that are no longer functioning. However, due to the limited number of organs for transplantation, interspecies transplants are performed, namely transplants between animals and humans called Xenotransplantation. Xenotransplantation is a technique of transplanting animal organs or tissues into human organs or tissues that can no longer function. Xenotransplantation can be one way to overcome the availability of transplant organs for humans. The most potential animal that can be used is the pig because it is almost similar to humans. However, xenotransplantation still causes problems due to immune rejection in the donor and the risk of transmission of infection. The purpose of writing this review article is to find out the potential, risks, and religious perspectives regarding xenotransplantation carried out in the health world. The method used in the preparation of this article is a literature study conducted by reviewing several journals, books and research articles related to xenotransplantation. To overcome the problems caused by xenotransplantation, genetic engineering is carried out in animals in order to produce more compatible organs. Thus, there are several successful organ xenotransplantation experiments although they still require further development. Ethically and legally, xenotransplantation is allowed as long as it is not abused and can save the patient. With the development of biotechnology, xenotransplantation is expected to be an alternative solution that can be used to overcome the scarcity of transplant organs in the future. So the use of xenotransplantation can potentially be an alternative solution that can be used to overcome the scarcity of transplant organs for humans. The risks resulting from the process can be reduced with further research to create animal organs that are suitable for the human body. In the perspective of Islam, xenotransplantation is allowed if it is done to save lives and not to abuse the animal.